The Enactment of Classroom Justice Through Explicit Instruction: Deciphering the Changes in English as a Foreign Language Teachers’ Perceptions and Practices - Estaji, Masoomeh; Zhaleh, Kiyana (Frontiers in Psychology, 2022)
This mixed methods research study investigated if explicit instruction could affect EFL teachers’ perceptions and practices of classroom justice considering its three-dimensional conceptualization, encompassing the distributive, interactional, and procedural justice. To this end, 77 Iranian English as a Foreign Language (EFL) teachers, chosen through maximum variation sampling, attended a four-session online justice-training course. The data were collected both before and after the course intervention through close- and open-ended questionnaires. Quantitative data analysis results, obtained through running paired samples t-tests and Wilcoxon signed ranks tests, indicated that except for the distributive component, the treatment was effective in significantly enhancing the Iranian EFL teachers’ procedural, interactional, and total classroom justice perceptions. Content analysis of the posttest qualitative data, done through MAXQDA, revealed that the participants approved the course usefulness, its significance, and uses of justice enactment strategies in their classroom. Furthermore, they confirmed positive changes in their conceptions and practices of justice because of attending the course and showed enthusiasm in attending more such courses in the future. The convergence of the quantitative and qualitative results in this study demonstrated the effectiveness of the justice-oriented training course for enhancing EFL teachers’ just classroom behaviors. Hence, the results would be fruitful for teacher educators aiming to promote the pre- and in-service EFL teachers’ professional effectiveness through explicit instruction on classroom justice and its use in teacher education programs.